DIAGNOSTIC PROBLEMS OF A MALE PATIENT WITH MIXED CONNECTIVE TISSUE DISEASE - Nina Oktafianti Marfu'ah (Current Internal Medicine Research and Practice Surabaya Journal, 2021)
Mixed connective tissue disease (MCTD) is an overlap disease, has been recognized as an entity disease with a mixture of clinical manifestations from systemic lupus erythematosus (SLE), systemic sclerosis (SSc), polymyositis/dermatomyositis, and rheumatoid arthritis, accompanied by the presence of high titers antibodies to U1 ribonucleoprotein (anti-U1RNP). We had reported case of a male patient who has chronic dysphagia, progressive dyspnea, and the presence of skin lesions. Based on the examination, it was found chronic dysphagia, progressive dyspnea caused by pneumonia and suspected interstitial lung disease, autoimmune hemolytic anemia, discoid lesions, and skin biopsy revealed scleroderma. This patient did not meet the diagnostic criteria of MCTD because anti-U1RNP examination had not been performed as one of the requirements in the diagnostic criteria. However, because he has strong signs and symptoms toward MCTD where there were overlapping symptoms of SLE as well as symptoms of SSc, so we diagnosed him as MCTD.